Pregestational diabetes alters cardiac structure and function of neonatal rats through developmental plasticity - Alam, Md Jahangir; Uppulapu, Shravan Kumar; Tiwari, Vikas; Varghese, Bincy; Mohammed, Soheb Anwar; Adela, Ramu; Arava, Sudheer Kumar; Banerjee, Sanjay K. (Frontiers in Cardiovascular Medicine, 2022)
Pregestational diabetes (PGDM) leads to developmental impairment, especially cardiac dysfunction, in their offspring. The hyperglycaemic microenvironment inside the uterus alters the cardiac plasticity characterized by electrical and structural remodelling of the heart. The altered expression of several transcription factors due to hyperglycaemia during foetal development might be responsible for molecular defects and phenotypic changes in the heart. The molecular mechanism of the developmental defects in the heart due to PGDM remains unclear. To understand the molecular defects in the two-days old neonatal rats, streptozotocin-induced diabetic female rats were bred with healthy male rats. We collected two-day-old hearts from the neonates and identified the molecular basis for phenotypic changes. Neonates from diabetic mothers showed altered electrocardiography and echocardiography parameters. Transcriptomic profiling of the RNA-seq data revealed that several altered genes were associated with heart development, myocardial fibrosis, cardiac conduction, and cell proliferation. Histopathology data showed the presence of focal cardiac fibrosis and increased cell proliferation in neonates from diabetic mothers. Thus, our results provide a comprehensive map of the cellular events and molecular pathways perturbed in the neonatal heart during PGDM. All of the molecular and structural changes lead to developmental plasticity in neonatal rat hearts and develop cardiac anomalies in their early life.